Comparison of Indicators of Families at Risk of Stunting in High-Income Regencies and Low-Income Regencies in East Nusa Tenggara Province - Lydia, Mona; Lada, Christina Olly; Roga, Anderias Umbu (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Stunting is a condition of failure to thrive in children due to chronic malnutrition. Early detection of various indicators of families at risk of stunting is an important effort in preventing stunting in the community. This research aims to analyze the comparison of indicators of families at risk of stunting in districts with high per capita income and districts with low per capita income. The Method is secondary data research. The data source is the results of the 2021 National Population and Family Planning Agency (BKKBN) Survey of East Nusa Tenggara Province. The sample size is 878 families divided into 439 families at risk of stunting from high-income districts per capita, and 439 families at risk of stunting from low-income districts. Sampling was carried out by stratification sampling technique or layered sampling. The independent variable is an indicator of a family at risk of stunting, namely the age of the mother, education, fixed income, number of children, sources of drinking water, proper latrines, and habitable houses, and the dependent variable is income per capita in the district where the family lives. The data were identified and statistically analyzed using bivariate Chi-Square test and multivariate logistic regression with a significant p-value <0.05. The result show that the chi-square test mother's age (p = 0.31), mother's education (p=0.77), fixed family income (p=0.00), number of children (p=0.17), availability of water sources clean (p=0.67), healthy latrine ownership (p=0.82), and healthy home ownership (p=0.03). Logistic regression test results for family fixed income (p=0.00), healthy home (p=0.07). The Conclusion is mother's age, mother's education, number of children, availability of clean water sources, ownership of latrines, and healthy homes are the main indicators of the risk of stunting in families. This indicator has no difference between families living in areas with low per capita income, and families living in areas with high incomes.